The Role of Geological Structures to Tunnel Inflow, Modelling Strategies and Predictions - Sharifzadeh, Mostafa; Javadi, M.; Zarei, H.
Comprehensive understanding of the field scale hydraulic behaviour of rock mass is critical to control of water inflow to underground excavations. In this paper, the geohydraulic modelling and characterization of geological structures respect to water inflow into tunnels are discussed. A conceptual model, a classification of inflow rate, and a framework of modelling method selection were proposed for evaluating the effects of different geological structures in heterogeneity, consequence, and modelling of groundwater inflow into tunnels, respectively. These geological structures are porosity, bedding, fracture, dyke, fold, fault, and karst. A meaningful trend of increasing in the flow rate, construction risks and difficulty, inflow locality, and hazards potential can be found in the change geological structures from porosity to karst. Due to the complexity of macro and pseudo-scale geological structures, empirical models based on the engineering geology linked with the fracture characterization can be adapted for more efficient predictions of groundwater inflow into tunnels.